Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy in Children: A Retrospective Analysis of 35 Cases - Fang, Hongjun; Hu, Wenjing; Jiang, Zhi; Yang, Haiyan; Liao, Hongmei; Yang, Liming; Wu, Liwen (Frontiers in Immunology, 2021)
Objective To analyze the clinical manifestations, imaging, electroencephalography, treatment, and prognosis of 35 cases of autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) in children. Methods Children hospitalized in the Department of Neurology, Hunan Children’s Hospital, China, between January 2015 and June 2021, owing to autoimmune diseases of the central nervous system were subjected to a cell-based assay (CBA). The assay identified 40 children positive for GFAP-immunoglobulin (Ig)G antibodies in the serum and/or the cerebrospinal fluid. Based on clinical manifestations and imaging characteristics, five children who were only positive for GFAP-IgG antibodies in serum were excluded, and the remaining 35 children were diagnosed with autoimmune GFAP-A. The clinical data derived from the 35 children were retrospectively analyzed. Results A total of 35 children, including 23 males and 12 females with a mean age of 6.3 ± 0.6 years, manifested clinical symptoms of fever (62.9%), headache (42.9%), convulsions (42.9%), abnormal mental behavior (51.4%), disorders of consciousness (54.3%), visual disturbance (22.9%), ataxia (11.4%), paralysis (40%), and autonomic dysfunction (25.7%). One child exhibited only the clinical symptom of peripheral facial nerve palsy. Eleven out of 35 children were also positive for other antibodies. In addition to the common overlapping autoimmune syndromes, one case of autoimmune GFAP-A also manifested as Bickerstaff’s brainstem encephalitis. Linear periventricular enhancement upon MRI was significantly less frequent in children (8.5%) than in adults. In pediatric patients, MRI contrast enhancement was principally seen in the meninges and brain lobes. Although repeated relapse (17.1%) and sequelae symptoms (20%) occurred in some cases, most children showed a favorable prognosis. Spearman’s rank correlation showed that the antibody titer was not significantly associated with the severity of the initial disease conditions. Conclusions The disease diagnosis in children seropositive for GFAP antibodies only should receive a comprehensive diagnosis based on their clinical symptoms, imaging, electroencephalographic characteristics, and treatment responses. Some patients with relapses should receive repeated gamma globulin and corticosteroid therapy or the addition of immunosuppressants to their therapeutic regimen, and slow-dose tapering of corticosteroids and extended treatment are recommended for patients with overlapping autoimmune syndromes.